THE ASSESSMENT AND REDUCTION OF CARDIAC EVENTS RISK IN NONCARDIAC OPERATIONS: IS THERE A NEED FOR REVIEW OF RECOMMENDATIONS? - A. N. Sumin (Рациональная фармакотерапия в кардиологии, 2015)
One of the pressing problems of modern cardiology is the cardiac complications risk evaluation and correction in noncardiac surgery. Recent international guidelines on this issue have focused on the pharmacological prevention of complications while reducing the preoperative examination and preventive revascularization. The reason for this experts position has been a series of studies DECREASE, performed in the Erasmus Medical Center (The Netherlands) under the supervision of Professor D. Poldermans. However, this summer the results of these studies have found no scientific value because of the significant irregularities in their conduct. It makes to have a new look at the problem of perioperative medicine, to rethink the available scientific evidence. In this review we discussed in detail the use of beta-blockers in noncardiac surgery in view of new circumstances.